Epidemiology of peer cybervictimization and its relationship with health-related quality of life in adolescents: A prospective study - González-Cabrera, Joaquín; Díaz-López, Adoración; Caba-Machado, Vanessa; Ortega-Barón, Jessica; Echezarraga, Ainara; Fernández-González, Liria; Machimbarrena, Juan Manuel (Journal of Adolescence, 2023)
Introduction: Research focused on the association between peer cybervictimization and declining health-related quality of life (HRQoL) is scarce. Currently, few longitudinal studies find an association between these phenomena, and none focus on cybervictimization profiles. The main objectives are: (1) to analyze the point and period prevalence, and incidence of cybervictimization profiles (uninvolved, new, ceased, intermittent, and stable cybervictims); (2) to study the relationship between cybervictimization and HRQoL over time; (3) to determine the longitudinal impact on the HRQoL of each type of profile. Methods: A prospective study was conducted in three waves over 13 months. A total of 1142 adolescents aged 11–18 years participated in all the waves (630 girls, 55.2%). Results: The prevalence of victimization for the three waves was 21.6% (Wave 1; W1), 23.5% (W2), and 19.6% (W3), respectively. The period prevalence was 41.3%, and the accumulated incidence was 25.1%. It was found that 24% of the participants were new victims, 5.9% were intermittent victims, and 6% were stable victims. Being a cybervictim at W1 poses a relative risk of 1.73 [1.29–2.32], that is, a twofold increased risk of presenting a low HRQoL 13 months later compared to those who are not cybervictims. Conclusion: One in four adolescents became a new cybervictim during the 13 months of the study. The adolescents who presented poorer HRQoL were the stable cybervictims.
Keywords: adolescents; cyberbullying; health-related quality of life; longitudinal; prevalence; profiles; Scopus; JCR